Effects of corn processing and dietary wet corn gluten feed on newly received and growing cattle - Siverson, Anna (Kansas State University, 2012)
Effects of corn processing with or without the inclusion of wet corn gluten feed (WCGF) on growth and performance were analyzed in two experiments. Treatments for both experiments were a diet including 47% whole-shelled corn (WSC) with no WCGF (WSC/0WCGF), a diet including 29% WSC with 30% WCGF (WSC/30WCGF), a diet including 47% dry-rolled corn (DRC) with no WCGF (DRC/0WCGF), and a diet with 29% DRC with 30% WCGF (DRC/30WCGF). Exp. 1 used 279 crossbred calves (230 kg) that were allocated to treatments in a 2x2 factorial completely randomized block design. No corn processing effects (all P > 0.31) were observed. Final BW was increased when WCGF was included in the diet (P = 0.03). ADG was increased for diets with WCGF (P = 0.03). Efficiency was not affected by the incorporation of WCGF in the diet. Digestibility of DM (P = 0.006) and starch (P = 0.009) was increased by the dietary inclusion of WCGF. There were no benefits observed for processing corn, but including WCGF at 30% (DM) increased gains and overall performance. Exp. 2 was a digestibility experiment using 5 ruminally cannulated Holstein heifers (248 ± 13 kg BW) in a 4 × 4 Latin square with an additional animal that was administered the same treatment sequence as another heifer on trial. No corn processing effects were observed for DM, starch, and ADF intake (all P ≥ 0.09). Dietary WCGF inclusion increased starch, non-starch and ADF intake (all P ≤ 0.01). Digestibility of DM, starch, non-starch, and ADF was not affected by corn processing, but DM, non-starch, and ADF digestibility were increased by WCGF inclusion in the diet (P ≤ 0.03). Ruminal pH was not affected by corn processing (P = 0.90) or dietary WCGF inclusion (P = 0.09). No corn × WCGF interactions were detected. There also was no difference among VFAs or total VFA concentration (all P ≥ 0.12) for corn processing effects. Passage rate (%/h) and ruminal liquid volume was not affected by corn processing or dietary WCGF inclusion (all P ≥ 0.66).
Keywords: Receiving cattle; Whole corn; Wet corn gluten feed; Animal Sciences (0475)